Determination of bisphenols in environmental water samples using polydopamine-coated magnetic Fe3O4 as a magnetic solid-phase extraction material coupled with high-performance liquid chromatography. Issue 16 (13th April 2016) - Ye, Qing; Chen, Zongbao; Liu, Linhai; Hong, Liming
Abstract : Fe3 O4 @polydopamine composites were synthesized and used as a magnetic adsorbent to extract bisphenols from environmental water samples before determination using HPLC. Abstract : Polydopamine-coated magnetic Fe3 O4 composite nanoparticles were synthesized via a simple solvothermal reaction and the self-polymerization of dopamine. The as-synthesized nanocomposites were successfully applied as an effective adsorbent for the pre-concentration of four bisphenols in environmental water samples prior to separation by high-performance liquid chromatography. The polydopamine-coated magnetic Fe3 O4 composites had several advantages over conventional adsorbents, such as a large surface area, fast separation ability, super-hydrophilicity and higher peak intensities for aromatic analytes. Various parameters, including the eluting solvent and volume, the amount of absorbents, the extraction time and the elution time, were optimized. Validation experiments showed that the optimized method had a good linearity ( r 2 > 0.9990), satisfactory precision (relative standard deviation < 6.2%) and a high recovery (92–105%). The limit of detection was 0.030–0.043 μg L −1 and the limit of quantification ranged from 0.10 to 0.14 μg L −1 . The results indicated that the proposed method has the advantages of convenience, good sensitivity and high efficiency. The method was successfully applied to the determination of bisphenols in real environmental water samples.